The Evolution of Concrete Microstructure and Chloride-Ion Diffusion Coefficient Under Cyclic Axial Compression - Qingzhang Zhang; Mengzhe Zhao; Li Song; Yuhang Yang; Jiaming He (International Journal of Concrete Structures and Materials)
Abstract The changes of the microscopic pore structure for concrete under cyclic axial compression accelerate chloride-ion penetration, reducing the durability of concrete structures. To address this, a chloride-ion migration experiment for concrete was conducted under cyclic axial compression, and the pore structure and pore group content of concrete were quantitatively characterized through equilibrium moisture content testing. In addition, a multiscale theoretical model for the chloride-ion diffusion coefficient in concrete was established based on the multiphase sphere model. The results show that cyclic loading forms an open hysteresis loop in the concrete's stress–strain curve, which evolves in the direction of increasing strain. Under loading, the microscopic pore structure of concrete coarsens, with an increase in the proportion of large capillary pores and gel pores, and a decrease in the proportion of small capillary pores. The model demonstrates good applicability when the chloride-ion diffusion coefficient is less than 22 × 10–12 m2/s. The model analysis indicates that the influence of cyclic axial compression loading on chloride-ion diffusion coefficient is more pronounced when the initial porosity ranges from 0.1 to 0.3. In addition, the more complex the microstructure of the concrete, the less its chloride-ion diffusion coefficient is affected by load-induced damage. At the same DI/Dm ratio, Dc/Dm gradually decreases with increase the volume fraction of coarse aggregates, but when DI/Dm reaches 15, the variation of Dc/Dm becomes negligible, approximately equal to 0.86. This indicates that when the ITZ exhibits a higher porosity content, the increased availability of chloride-ion transport pathways counteracts the blocking effect of coarse aggregates on chloride ions.